2020
DOI: 10.1007/s00415-020-09795-3
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke and dose adjustment of oral Factor Xa inhibitors in patients with atrial fibrillation

Abstract: Background Oral Factor Xa inhibitors for the prevention of stroke in atrial fibrillation require dose adjustment based on certain clinical criteria, but the off-label use of the reduced doses is common. Methods Data from an observational registry including patients admitted with acute cerebral ischemia while taking oral Factor Xa inhibitors for atrial fibrillation between April 2016 and December 2018 were investigated. The dose regimen of the Xa inhibitor was classified as "appropriate", "underdosed" and "over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…This finding is in line with a German single-center observation based on 254 acute stroke patients with known AF, reporting an off-label dose in one out of three patients on factor Xa inhibitors. [32] In the Berlin Atrial Fibrillation Registry, under-dosing of apixaban and rivaroxaban at stroke onset was associated with old age, which is in line with prospective AF registries like ORBIT AF II, including only a subset of patients with prior (but not acute) ischemic stroke [14][15][16][17]. Compared to on-label dosing, under-dosing of apixaban or rivaroxaban was not significantly associated with stroke severity on hospital admission or at hospital discharge.…”
Section: Discussionsupporting
confidence: 68%
“…This finding is in line with a German single-center observation based on 254 acute stroke patients with known AF, reporting an off-label dose in one out of three patients on factor Xa inhibitors. [32] In the Berlin Atrial Fibrillation Registry, under-dosing of apixaban and rivaroxaban at stroke onset was associated with old age, which is in line with prospective AF registries like ORBIT AF II, including only a subset of patients with prior (but not acute) ischemic stroke [14][15][16][17]. Compared to on-label dosing, under-dosing of apixaban or rivaroxaban was not significantly associated with stroke severity on hospital admission or at hospital discharge.…”
Section: Discussionsupporting
confidence: 68%
“…Rivaroxaban, the factor Xa inhibitor with the most variable available doses in different indications [ 16 ], was the NOAC showing the highest rate of medication errors. Another study recently reported a rate of up to 65% of patients with Factor Xa inhibitor treatment having received an inappropriate dose regimen before stroke [ 17 ]. Furthermore, lower plasma levels at admissions were associated with greater stroke severity [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study recently reported a rate of up to 65% of patients with Factor Xa inhibitor treatment having received an inappropriate dose regimen before stroke [ 17 ]. Furthermore, lower plasma levels at admissions were associated with greater stroke severity [ 17 , 18 ]. Although different available doses principally enhance the possibility to better tailor individual medications, our data underline the growing need to educate prescribing physicians.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study on 1124 atrial fibrillation patients aged 85 years and older treated with vitamin K antagonists (58.7%) or DOACs (41.3%), no thrombotic events occurred in the small group of underdosed DOAC patients. 88 Recent studies demonstrated that oFXaIs' underdosing was associated with a higher stroke severity in patients admitted with ischaemic stroke, 89 and with a higher rate of major vascular occlusion in patients admitted with suspected ischaemic stroke. 90 In conclusion, despite inherent limitations of observational studies, and with few exceptions, 40,86,88 there is consistent evidence that underdosing of oFXaIs is not associated with a significant reduction of bleeding events and is possibly associated with an increased risk of thromboembolic events.…”
Section: Clinical Implications Of Oral Factor Xa Inhibitors' Underdosing On Safety and Efficacy Outcomesmentioning
confidence: 99%